Phytoliths as a tool for archaeobotanical, palaeobotanical and palaeoecological studies in Amazonian palms - Morcote-Ríos, Gaspar; Bernal, Rodrigo; Raz, Lauren (Botanical journal of the Linnean Society, 2016)
Abstract Phytoliths are silica bodies found in vascular plants, often diagnostic at the family level in angiosperms. They are especially abundant in palms (Arecaceae), occurring in all organs, with the highest concentrations in leaves. Phytoliths can remain in the soil for thousands or even millions of years, providing physical evidence of taxa in time and space. As such, they can be used to reconstruct ancient floras and landscapes, interpret events in plant evolution and document plant use by ancient peoples. In palms, studies of phytoliths remain scarce and guides for identifying those of regional floras are needed, especially in the Amazon, where palms are a dominant floristic and cultural element. We surveyed contemporary phytoliths in 92 species of Amazonian palms, representing 29 genera across four subfamilies. Previous studies have recognized only two palm phytolith morphotypes (globular echinate and conical), but here we recognize eight types that provide diagnostic information at the levels of subfamily, tribe, genus and, in some cases, species. With this degree of taxonomic resolution, phytoliths are proving to be a powerful line of evidence linking palms to past human activity in Amazonia and we expect their use to be expanded to interpret palaeoecological changes in this region across geological time.